2015
DOI: 10.15252/msb.20145504
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analyses reveal distinct chromatin‐associated and soluble transcription factor complexes

Abstract: The current knowledge on how transcription factors (TFs), the ultimate targets and executors of cellular signalling pathways, are regulated by protein–protein interactions remains limited. Here, we performed proteomics analyses of soluble and chromatin-associated complexes of 56 TFs, including the targets of many signalling pathways involved in development and cancer, and 37 members of the Forkhead box (FOX) TF family. Using tandem affinity purification followed by mass spectrometry (TAP/MS), we performed 214 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
131
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(154 citation statements)
references
References 85 publications
8
131
0
Order By: Relevance
“…7E). Recent studies have shown that the FOX transcription factors can interact with different protein complexes when they are "on" or "off" the chromatin (46,47). This study suggests that the recruitment of co-regulatory proteins to the transcription factors determines their transcriptionally dependent and independent functions.…”
Section: Discussionmentioning
confidence: 88%
“…7E). Recent studies have shown that the FOX transcription factors can interact with different protein complexes when they are "on" or "off" the chromatin (46,47). This study suggests that the recruitment of co-regulatory proteins to the transcription factors determines their transcriptionally dependent and independent functions.…”
Section: Discussionmentioning
confidence: 88%
“…8C) where a net increase of BCL11B-P300 interaction is clearly seen, the impact of T-cell activation on BCL11B-MTA1 interaction is relatively low. However, in contrast with Co-IPs, the ChIP experiments were performed on chromatin and are thus more likely to reflect the function of a transcription factor and of its different partners in their natural context (53,54). In developing murine thymocytes, BCL11B and MTA1 remained associated at the Id2 promoter both in basal conditions and activating conditions, as shown by ChIP experiments (21).…”
Section: Discussionmentioning
confidence: 99%
“…Our question arose because we were surprised to find that many proteins associated with NFAT5, which is a transcription factor, have functions not obviously related to transcription, such as ribosome/ (35), 197 (23.5%) fall into one or more of the five categories, which is lower than among our 467 preys. Also, preys analyzed separately in soluble and chromatin bound nuclear extracts (35), which we combined, include more proteins in the five categories (P ϭ ϳ0.002, one tailed Fisher's exact test) in the soluble fraction (77 out of 256, 30.1%), than in the chromatin bound fraction (120/583, 20.6%). We conclude that relatively few of the proteins pulled down by peptide baits from NFAT5 are associated with transcription factors in general and may therefore be specific to NFAT5.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly more (P Ͻ 0.0001, one-tailed Fisher's exact test) preys in these categories are from our cytoplasmic extracts (165 out of 254, 65.0%) than from our nuclear extracts (98 out of 283, 34.6%). To look into our question we compared the proteins pulled down by the NFAT5 peptide baits in our experiment to the proteins contained in complexes with 56 other transcription factors(35) or with the transcription factor IRF1(44). Among 839 preys associated with all 56 transcription factors…”
mentioning
confidence: 99%